1632f Varied criteria for work-related upper extremity disorders in united states. (24th April 2018) - Rempel, D; Hegmann, K; Meister, R
Abstract : In the US, the acceptance of a claim for a work-related MSD is most commonly determined by the employer and insurance carrier with input from the physician's report. For most workers, the process is based on state laws, which vary from state to state. Some states (e.g., California) have adopted the ACOEM Medical Practice Guidelines (2nd Ed, 1). The Guidelines recommend a process for determining work-relatedness based on evidence of disease, evidence of exposure, epidemiology, and other factors (e.g., non-workplace exposures). For example, the diagnosis of carpal tunnel syndrome (CTS) should consider the presence of numbness/tingling in the median nerve distribution, electrodiagnostic studies (EDS), if available, and non-work factors such as age and BMI. Work-relatedness for CTS and other non-traumatic hand/wrist disorders (e.g., tendinosis, tendinitis, trigger digit) generally requires sustained or repeated forceful (>10N) pinching or gripping and the Guidelines refer to the ACGIH HAL TLV as a risk assessment tool. Other MSDs discussed include epcondylalgia (epicondylosis), ligament sprains, tenosynovitis/tendinosis (including 0de Quervain's), trigger digit, hand arm vibration syndrome (HAVS), ulnar and radial nerve entrapment, ganglion cyst and non-specific hand/wrist/forearm pain. Colorado State developed treatment guidelines for CTS (38-pages), with provisions that are enforceable under workers' compensation rules (2). The roles of history, physical examination and EDS in diagnosis and management are spelled out. For determining work-relatedness, job title alone is not sufficient. Six specific ergonomic hazards, with minimum daily exposure durations (e.g., pinching >18 n more than 3 hour per day) are listed. Washington State has a 13-page diagnosis and treatment guideline for CTS. Diagnosis requires both appropriate symptoms and an abnormal EDS. Work-related risk factors are listed but without the exposure thresholds provided in the Colorado guidelines. Thus, determinations of worker's compensation cases vary from state to state and these differences could influence comparative research studies.